DEVELOPMENT HISTORY OF LANDSCAPE SCIENCE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
History of the development of the science of the basics of landscape science, Concepts of landscape, Landscape components and landscape-forming factors, Morphological structure and internal relationships of landscapes, Dynamics and development conditions of landscapes, Energy flow and moisture circulation in landscapes, Biogeochemical circulation of matter in landscapes, Geochemistry and geophysics of landscapes, Classification of landscapes, understanding of anthropogenic landscapes and its types, emergence and development of applied landscape science, landscape forecasting, landscape protection, natural geographic zoning issues are widely covered.